(untitled) (Revista de Ciências Agroveterinárias, 2008)
The Campanha region of Rio Grande do Sul, southern Brazil, has large areas of natural fields destined to livestock. In this agro ecosystem, the dung beetle actuation as controllers of cattle parasites, by dung bovine decomposition utilized for alimentary and nidification resources, is important. A survey of copronecrophagous Scarabaeidae species occurrence in natural fields of southern Brazil was carried out from December of 2006 to November of 2007. Eight pitfall traps were assembled, using human dung and bovine liver in decomposition as bates. A total of 565 dung beetles, belonging to 18 species, were collected, with most prominence to Onthophagus hirculus and Canthon ornatus bipunctatus. The coprophagy was the most frequent feeding habit among species. Onthophagus hirculus, Canthon ornatus bipunctatus, Ontherus sulcator e Canthidium moestum are the species with greater potential to be utilized in cattle dung management in the south region of Rio Grande do Sul.